Sports nutrition and mental toughness in athletes: a systematic review of mechanistic evidence - Humaedi Humaedi; Andi Saparia; Syahputra Manik; Satria Yudi Gontara; Andi Sultan Brilin Susandi Eka Wahyudhi (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
The relationship between sports nutrition and psychological performance has become an important area in sport science. This systematic literature review (SLR) examined the role of sports nutrition in enhancing mental toughness, psychological resilience, and athletic performance. The review followed the PRISMA 2020 guidelines and employed a structured Boolean search in the Scopus database. Peer-reviewed articles published between 2020 and 2026 were screened. From 411 identified records, 10 studies met the inclusion criteria and were included in the final synthesis. Findings revealed that adequate carbohydrate and protein intake supports neurocognitive functions related to perceived effort and decision-making. Furthermore, targeted supplementation, including branched-chain amino acids, antioxidants, and probiotics, contributes to recovery processes that may reduce anxiety and burnout risk. The review also identified gender-related nutritional disparities and highlighted the gut–brain axis as a promising but underexplored mechanism influencing mental resilience. Overall, nutrition represents a modifiable factor that can strengthen athletes’ psychological performance and mental toughness.